Growth, gas exchange and function of antioxidant defense system in two contrasting rice genotypes under Zn and Fe deficiency and hypoxia - Hajiboland, Roghieh; Beiramzadeh, Naiere (Acta Biologica Szegediensis, 2008)
For study of underlying physiological mechanisms for genotypic differences in tolerance to Zn and Fe deficiency and hypoxia, two contrasting rice genotypes (Oryza sativa L. cv. Amol and Dashti) were studied in nutrient solution with or without aeration. Growth of the lowland genotype (Amol) was significantly improved in nutrient solution without aeration, the opposite was observed for upland genotype (Dashti). Tolerance of Amol to low Zn was higher than Dashti, in contrast the former genotype was more susceptible to Fe deficiency. Photo-chemistry of leaves was affected strongly by Fe but not Zn deficiency. Low supply of Zn and Fe impaired photosynthetic capacity of plants mainly via stomatal limitation and the amount of reduction in net assimilation rate correlated well with differential growth reduction under Zn and Fe deficiency stress. Under hypoxia, plants had lower stomatal conductance and transpiration rate leading to improved photosynthetic water use efficiency. Activity of ascorbate peroxidase (APX) and guaiacol peroxidase (POD) induced by low Zn supply, but low Fe caused reduction of APX, CAT and POD. Activity of SOD decreased in low Zn plants, but increased in plants suffered from Fe deficiency. Increased APX activity in response to hypoxic conditions in Amol was associated with higher tolerance in this genotype, in contrast POD activity only monitored stress conditions without any protecting role. A close correlation was observed between accumulation of O2.– and differential sensitivity of genotypes to hypoxia.